The Accuracy of English Grammatical Morpheme Orders among Chinese EFL Learners and Instructor Interventions - Wang, Xianyuan; Lau, Su Kia; Chew, Fong Peng; Saeed, Murad Abdu; Cao, Xuejin (Jurnal Arbitrer, 2024)
In the domain of first and second language (L1/L2) acquisition, Morpheme Order Studies (MOS) encapsulate a body of influential research. This study specifically aimed to (1) assess the accuracy of nine grammatical morphemes used by Chinese learners of English as a Foreign Language (EFL) in their compositions, (2) investigate the factors affecting the accurate use of these morphemes among Chinese EFL learners, and (3) explore the interventions implemented by their instructors to assist the Chinese EFL learners in accurately using these intricate grammatical constructs. Employing the Target-Like Use methodology, the data were collected from the essays of 108 high school learners in Kunming, Yunnan, China, to ascertain the order of their accuracy in using these morphemes. Subsequently, a semi-structured interview was conducted with five EFL instructors and 15 tested learners to delve into the factors influencing their proficiency with specific complex morphemes and the application of instructional interventions used by the instructors. The findings of the study revealed that the learners did not consistently adhere to Krashen’s hypothesized natural order; rather, they exhibited idiosyncratic acquisition patterns. Particularly, it was noteworthy that there was a relatively low accuracy observed in the usage of certain morphemes, such as irregular past and 3rd person singular –s (features absent in the learners’ native language). Furthermore, factors contributing to the diminished accuracy of these specific morphemes include the learners’ mother tongue interference in their use of these morphemes, syntactic and semantic complexities, motivational factors, environmental factors, and limited output of specific morphemes. Additionally, the research uncovered various interventions such as peer review, storytelling, and incorporating songs employed by the EFL instructors to assist the Chinese EFL learners in using these challenging grammatical morphemes correctly. This study provides valuable insights for EFL students, instructors, curriculum developers, and textbook editors.